Traumatic spinal cord injury: neurologic and functional recovery. - Andrade, Maria João (2008)
A retrospective study was conducted.Evaluate the neurologic and functional recovery in patients with Traumatic Spinal Cord Injury (TSCI).A retrospective study was conducted, including the 93 patients with a diagnosis of TSCI admitted for rehabilitation in the Physical and Rehabilitation Medicine Department, Santo António General Hospital, between January 1993 and December 2002. Demographic and clinical data were collected from the hospital charts. The patients were evaluated at admission for rehabilitation, before discharging, 1 year and 3 years after injury. Neurologic status was registered according to the standards of the American Spinal Injury Association (ASIA) and functional status by the Functional Independence Measure (FIM).The sample population was 87% men, with a mean age of 40 years. Motor vehicle accidents and falls were the commonest mechanism of injury. The majority sustained dorsal and cervical lesions (45% and 42% respectively). The initial management included: intravenous high dose methylprednisolone, administered within eight hours after injury in 54% of the sample; early surgical stabilization, performed on 77%. Incomplete cord injury carried a better prognosis of motor improvement, especially the patients classified as C on the ASIA Impairment Scale (AIS). A significant statistical association was found between the outcomes obtained during the initial rehabilitation, and the ones achieved on the 3 year followup period. The neurologic recovery was not related with the patient's age, injury level, high dose steroid administration or surgery performed in the first 24 hours after injury (p >0.05). The FIM scores demonstrated the favourable functional outcomes achieved, especially during the inpatient rehabilitation.The results of this study further demonstrate the considerable potential for neurologic recovery after TSCI, emphasizing the importance of the rehabilitation investment continuity, especially for the ones with incomplete cord injury.